4H Project Guide: Swine Nutrition - Robert O. Myer; Joel H. Brendemuhl (EDIS)
A dependable and economical source of feed is the basis of a profitable hog operation. In fact, 40 to 60% of the total cost of producing hogs is feed. Thus, 4-Hers who raise hogs need to be keenly aware of the types of feed available. This document is 4H225, one of a series of the Animal Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 1, 1988 as 4HSR-17. Reviewed May 8, 2003.